A network meta-analysis of nonsmall-cell lung cancer patients with an activating EGFR mutation: Should osimertinib be the first-line treatment?. Issue 30 (July 2018) - Lin, Jia-Zhou; Ma, Song-Kun; Wu, Sheng-Xi; Yu, Shu-Han; Li, Xu-Yuan
Abstract: Background: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are the preferred first-line treatment for nonsmall-cell lung cancer (NSCLC) patients with an activating EGFR mutation. Osimertinib, compared with erlotinib or gefitinib, showed an improvement in progression-free survival (PFS) in a recent trial. The authors compared EGFR TKIs in terms of PFS in a network meta-analysis. Methods: The PubMed and Embase databases and meeting abstracts were screened for relevant studies between January 2009 and November 2017. A random-effect frequentist network meta-analysis model was conducted to assess PFS. P-score was used to rank treatment effects. Results: Eleven trials with 3145 patients and 5 TKIs (gefitinib, erlotinib, afatinib, dacomitinib, and osimertinib) were included. Heterogeneity and inconsistency existed in the network analysis. Gefitinib and erlotinib had similar effects (hazard ratio [HR] 0.94, 95% confidence interval [CI] 0.76–1.15). For all patients, the 3 TKIs with the highest probability of benefit were osimertinib, dacomitinib, and afatinib, with P-scores of 91%, 78%, and 46%, respectively. Compared with erlotinib or gefitinib, osimertinib was associated with improvement in men (HR = 0.79, 95% CI, 0.68–0.92), non-Asians (HR = 0.63, 95% CI, 0.40–0.98), smokers (HR = 0.73, 95% CI, 0.56–0.95), and those with a Del19 mutation (HR = 0.69, 95% CI, 0.54–0.90); dacomitinib and afatinib showed no improvement. Toxicity profiles mostly overlapped in all the EGFR TKIs. Toxicity-related death was rare. Conclusions: Osimertinib was shown to be the best agent to achieve the longest PFS in NSCLC patients with an activating EGFR mutation. However, the benefit of osimertinib might be restricted to certain subgroups.